2011
DOI: 10.1155/2011/170196
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Chemistry of Eremanthine: A Sesquiterpene Lactone with Relevant Biological Activity

Abstract: The several aspects on the chemistry of eremanthine such as isolation, structural classification, biological activity, synthesis, and chemical transformations in other sesquiterpene lactones are described in this review. The main publications on this sesquiterpenolide, from its isolation of natural sources in 1972 to the current days, are included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 159 publications
(182 reference statements)
0
4
0
Order By: Relevance
“…Dehydrocostus lactone, a guaianolide originally derived from S. lappa, can be produced through chemical transformations of eremanthine [41].…”
Section: Discussionmentioning
confidence: 99%
“…Dehydrocostus lactone, a guaianolide originally derived from S. lappa, can be produced through chemical transformations of eremanthine [41].…”
Section: Discussionmentioning
confidence: 99%
“…Germacranolides, such as compounds 22 – 24 , are characteristic metabolites in the genus Liriodendron , whereas the elemanolide dehydrotemisin was found in the species for the first time. Elemanolides represent a small group of sesquiterpene lactones that are biogenetically derived from germacranolides …”
Section: Resultsmentioning
confidence: 99%
“…Cos, a sesqu it er p ene lactone t hat cont a i ns a n α-methylene-γ-lactone ring structure, belongs to a class of compounds that react with enzymes containing thiol groups and their functional proteases, and interfere with the key biological processes of cells, exhibiting a variety of pharmacological activities (25). It has been reported that cos exerts a strong inhibitory effect on the proliferation and apoptosis of a variety of tumor cells at concentrations ranging between 2.5 and 40 µmol/l (15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%